2018
DOI: 10.5539/ibr.v11n2p103
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Governance and Innovative Strategies in Italian Family SMEs: Evidence from Tuscany

Abstract: Governance in family businesses is a relatively recent research topic in the field of management studies. Much research has sought to shed light on the factors that shape the relationship between governance structures and corporate strategies. Nevertheless, very little research has specifically addressed the relationships between the configuration of the Board of Directors and the firm's willingness to carry out innovative strategies. Our study aims to shed light on the relationship between the corporate gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This study found similarities across Sundanese small industries such that, in general, they could survive across generations because the strength of traditional Sundanese cultural traditions is translated through the intrinsic values of entrepreneurs into their business activities. In addition, there are several other important factors that determine longevity [11][12][13]. In the Sundanese ethnicity, the tradition of high long-term orientation, highcollectivism, low power distance, and high indulgence positively contribute to the longevity of small industry in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found similarities across Sundanese small industries such that, in general, they could survive across generations because the strength of traditional Sundanese cultural traditions is translated through the intrinsic values of entrepreneurs into their business activities. In addition, there are several other important factors that determine longevity [11][12][13]. In the Sundanese ethnicity, the tradition of high long-term orientation, highcollectivism, low power distance, and high indulgence positively contribute to the longevity of small industry in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Success stories of businesses in other countries surviving across generations because of the strength of their traditions were also reported in previous studies. For example, the strength of tradition and innovation are survival strategies for family businesses in Japan [11], local traditions and succession planning are the key to the survival of small businesses in Italy [12], and some Chinese culture and traditions, such as guanxi, play an important role in entrepreneurship [13]. Cultural traditions play a role in supporting business innovation in Thailand [14].…”
Section: Introductionmentioning
confidence: 99%
“…These peculiarities of family business innovation and entrepreneurship create further paradoxical tensions (Erdogan et al, 2019). On the one hand, continuous renewal and entrepreneurship are cornerstones of sustainable competitiveness (Kallmuenzer and Scholl-Grissemann, 2017;Nikolakis et al, 2022); on the other hand, tradition (Bonti and Cori, 2018) creates a tendency to conserve the status quo.…”
Section: Background and Motivationmentioning
confidence: 99%
“…The survival of the family business, and therefore its longevity over time, is, therefore, the result of a subtle exercise of balancing innovation and tradition (Bonti and Cori, 2013).…”
Section: Literature Background and Research Questionsmentioning
confidence: 99%
“…Several prior studies have addressed this topic, highlighting a number of factors which explain family business longevity, specifically highlighting the importance of balancing innovation and tradition (Corbetta and Salvato, 2012;Bonti and Cori, 2013). Overall, available studies have mainly focused on the endogenous dynamics of family businesses as drivers of longevity while effectively neglecting consideration of exogenous dynamics (Fernández-Moya, Fernández Perez and Lubinski, 2020).…”
Section: Introductionmentioning
confidence: 99%